SYARIAH DALAM KONTEKS NEGARA MODERN DI DUNIA ISLAM - Mazro’atus Sa’adah (UNIDA Gontor, 2018)
Discussions about sharia, especially Islamic political issues, were never discussed from the time of the Apostles until now. In the 1970s the power of Islam rose almost throughout the Islamic world. The Arab Spring affirms the importance of sharia enforcement. Many constitutions in the Muslim World include Islamic law clauses as the highest law. This issue will see how important it is to understand sharia, Islamic law, and fiqh, which will later become the basis for determining the typology of the State and related to the entry of sharia as its constitution. This article will also discusses the modernization of family law carried out by several Islamic countries, as a form of strengthening that Islam accepts modernization and not westernization.